Exploring the experiences of the team members in the interprofessional socialization process for becoming an interprofessional collaborator - Fatemeh Keshmiri (BMC, 2022)
Abstract Background The current study aimed to explore the team members' experiences in the socialization process for becoming a collaborator in an interprofessional team. Method This qualitative study is conducted using an inductive qualitative content analysis approach. Participants consisted of 32 physicians (n = 16) and nurses (n = 16) who participated by purposeful sampling. Data were collected through in-depth semi-structured interviews and analyzed by Graneheim and Lundman approach. Results In the study, "the perceived confrontation between interprofessional professionalism and uni-professionalism in the interprofessional socialization process" is explored as the theme, including two categories: "interprofessional professionalism commitment" as a facilitator and "uni-professional centrism" as a barrier. Conclusion A reciprocal dimension in interprofessional socialization was explored. Interprofessional professionalism adherence and team-centered accountability among team members were explored as a facilitator. The uni-professional culture and immature interprofessional collaboration competencies of team members disrupted the interprofessional socialization process.